2001
DOI: 10.1074/jbc.m103862200
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II-induced Transcriptional Activation of the Cyclin D1 Gene Is Mediated by Egr-1 in CHO-AT1A Cells

Abstract: Cyclin D1 protein expression is regulated by mitogenic stimuli and is a critical component in the regulation of G 1 to S phase progression of the cell cycle. Angiotensin II (Ang II) binds to specific G protein-coupled receptors and is mitogenic in Chinese hamster ovary cells stably expressing the rat vascular Ang II type 1A receptor (CHO-AT 1A ). We recently reported that in these cells, Ang II induced cyclin D1 promoter activation and protein expression in a phosphatidylinositol 3-kinase (PI3K)-, SHP-2-, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
57
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 79 publications
3
57
0
Order By: Relevance
“…Meanwhile, the oligo 3′ probe containing the binding site of the consensus SP1 was supershifted by anti-SP1 antibody but not by anti-EGR1 or anti-AP2 antibodies (data not shown). These results are consistent with previous studies showing binding of EGR1 to an overlapping EGR1/ SP1 site without displacement of SP1 in the human Ccnd1 promoter [26,27].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Meanwhile, the oligo 3′ probe containing the binding site of the consensus SP1 was supershifted by anti-SP1 antibody but not by anti-EGR1 or anti-AP2 antibodies (data not shown). These results are consistent with previous studies showing binding of EGR1 to an overlapping EGR1/ SP1 site without displacement of SP1 in the human Ccnd1 promoter [26,27].…”
Section: Discussionsupporting
confidence: 93%
“…Results of the promoter analysis revealed that the region between −174 and −73 was largely involved in Ccnd1 promoter activity, implicating this region as a major exendin-4-responsive element. The importance of this region has also been emphasised in human Ccnd1 promoters of oesophageal squamous carcinoma [26] and of Chinese hamster ovary cells stably overexpressing angiotensin II type 1A receptor [27]. Meanwhile, other cis-regulatory elements located between −73 and +130 of the promoter also appear to be involved in promoter activities in response to exendin-4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once activated, Egr-1 regulates the expression of several genes, including monocyte chemotactic protein-1 (MCP-1), platelet-derived growth factor (PDGF) A and B [7,9,10], and Cyclin D1 [11,12]. Previous studies showed that mechanical injury-induced up-regulation of Egr-1 is through activation of extracellular signal-regulated kinase (ERK), a key transducer of extracellular signals that promote cell growth and movement, which are critical for the initiation and progression of vascular lesions [13].…”
Section: Introductionmentioning
confidence: 99%
“…ERK transmits mitogenic signals by translocation to the nucleus where many of its substrates, including transcription factors, Egr-1, c-Fos and Elk-1 are activated [16][17][18]. Since Egr-1 induces the expression of multiple genes implicated in pathogenesis of atherosclerosis and restenosis after angioplasty [11,12,19], indicating that blocking of ERK/Egr-1 signaling pathway might be an important therapeutic strategy in reducing the incidence of restenosis after angioplasty.…”
Section: Introductionmentioning
confidence: 99%